2009
DOI: 10.1111/j.1365-2745.2009.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

An idealized model for tree–grass coexistence in savannas: the role of life stage structure and fire disturbances

Abstract: Summary1. We discuss a simple implicit-space model for the competition of trees and grasses in an idealized savanna environment. The model represents patch occupancy dynamics within the habitat and introduces life stage structure in the tree population, namely adults and seedlings. A tree can be outcompeted by grasses only as long as it is a seedling. 2. The model is able to predict grassland, forest, savanna and bistability between forest and grassland, depending on the different characteristics of the ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 62 publications
(131 reference statements)
2
84
0
2
Order By: Relevance
“…In state-and-transition models multiple stable states are possible, and the rangeland dynamics is explained through transitions (reversible or irreversible and abrupt) due to disturbances between steady states. The existence of multiple stable states has been pointed out by Dublin (1995), van de Koppel et al (1997), Anderies et al (2002), van Langevelde et al (2003), D'Odorico et al (2006), Hanan et al (2008), Okin et al (2009), Baudena et al (2010).…”
Section: What Is Special About the Savanna Environment That Allows Trmentioning
confidence: 96%
See 1 more Smart Citation
“…In state-and-transition models multiple stable states are possible, and the rangeland dynamics is explained through transitions (reversible or irreversible and abrupt) due to disturbances between steady states. The existence of multiple stable states has been pointed out by Dublin (1995), van de Koppel et al (1997), Anderies et al (2002), van Langevelde et al (2003), D'Odorico et al (2006), Hanan et al (2008), Okin et al (2009), Baudena et al (2010).…”
Section: What Is Special About the Savanna Environment That Allows Trmentioning
confidence: 96%
“…Fire has been explicitly included in many savanna models (Hochberg et al, 1994, Anderies et al, 2002, van Langevelde et al, 2003, D'Odorico et al, 2006, Beckage et al, 2009) and has often been -5-described as dependent on the availability of fuel load, that in arid ecosystem is given by dead grass. Hanan et al (2008) and Baudena et al (2010) have considered explicitly the demography of trees underlining the asymmetry of the fire effects between saplings and adult trees. This asymmetry can allow the survivorship of trees population at low densities thanks to mechanisms of 'storage effect' that compensate the loss of young trees due to demographic bottlenecks with the very low mortality of adult trees (Warner and Chesson, 1985).…”
Section: What Is Special About the Savanna Environment That Allows Trmentioning
confidence: 99%
“…A large number of experimental and modeling studies have focused on the tree-grass co-existence from an ecological perspective (e.g., Higgins et al, 2000;Sankaran et al, 2005;Baudena et al, 2010), thereby mainly focusing on cover and far less…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Our approach of age classing modeling, in which the vegetation increases its biomass while keeping the same structure, is similar to models using tree seedlings and adult trees (e.g., Scheiter and Higgins, 2009;Baudena et al, 2010). Baudena et al (2010) found that tree seedlings compete for the same water as grasses, while adult trees can outcompete grass, as it has deeper roots.…”
mentioning
confidence: 84%
See 1 more Smart Citation